2020
DOI: 10.1097/mpg.0000000000002677
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Ultrasound Scan Predicts Corticosteroid Failure in Children With Acute Severe Colitis

Abstract: Background and objective: Acute severe colitis (ASC) is a potentially life-threatening event. Optimal timing for second-line treatment in children is mainly based on the clinical score Pediatric Ulcerative Colitis Activity Index. The aim of our study was to evaluate the potential role of bowel ultrasound scan (BUS) in predicting the need of second-line therapy in ASC. Methods: Patients younger than 18 years admitted to a single tertiary referral center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“… 22 In UC, IUS response can be detected after 10–14 days, 40 , 45 possibly even earlier. 55 Such rapid rates of improvement have not been reported for biologics or immunomodulators. Two years after treatment initiation with either anti-tumour necrosis factor [TNF] or azathioprine, Castiglione et al .…”
Section: Resultsmentioning
confidence: 99%
“… 22 In UC, IUS response can be detected after 10–14 days, 40 , 45 possibly even earlier. 55 Such rapid rates of improvement have not been reported for biologics or immunomodulators. Two years after treatment initiation with either anti-tumour necrosis factor [TNF] or azathioprine, Castiglione et al .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, US has proven to be a valuable tool, particularly as a first line choice, during severe disease even at the patient's bedside. 10,12,19 In contrast, CCE has demonstrated excellent accuracy in assessing the extent of disease and distinguishing between mild and moderate-severe disease. However, it has shown a lower accuracy in identifying moderate disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been previously reported that US may be less accurate in detecting mild disease, as it may not identify superficial mucosal lesions such as erythema and mild friability. Nonetheless, US has proven to be a valuable tool, particularly as a first line choice, during severe disease even at the patient's bedside 10,12,19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a retrospective study including 69 ASUC episodes in 52 paediatric patients, salvage therapy was more frequently needed in patients with higher BWT, higher vascularisation, and loss of BWS at admission. A thickened wall (>3.4 mm) and loss of BWS were independent predictors of steroid resistance [ 67 ]. Thus, if IUS parameters prove to be independent predictors of response to systemic steroids in the ASUC setting, early IUS could enable a timelier introduction of salvage therapy.…”
Section: Evaluating Disease-related Complicationsmentioning
confidence: 99%